Crystallization in Multiphase Polymer Systems 2018
DOI: 10.1016/b978-0-12-809453-2.00010-4
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Polymer Nanocomposites

Abstract: This chapter is an overview of theeffect of the different nanofillers in the crystallization performance of polymer matrices. The mostrelevantnanocomposites were classified according to the natureofthereinforcement. In general, it was reported that the way of processing highly affect the crystal sizes, crystalline structure and the degree of crystallinity of semicrystalline polymer nanocomposites, then modifying the performance of the material. Therefore, the influence of differentcrystallization processesonba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Evidentemente, la naturaleza química de la superficie de la BNC, y por ende su dispersabilidad y compatibilidad relativa con la matriz hidrofóbica de PLA, jugó un rol fundamental en controlar la posibilidad de cristalización del poliéster. Lo anterior es, probablemente, una consecuencia de fenómenos contrapuestos asociados a i) la difusión y plegado de las cadenas de PLA que se ven parcialmente impedidos como consecuencia de la compatibilización (Cyras, D' Amico, & Manfredi, 2017), y ii) los efectos de nucleación inducidos por la dispersión relativa de los refuerzos. (Dai, Cao, & Wang, 2016;Teixeira et al, 2014).…”
Section: Resultados Y Discusiónunclassified
“…Evidentemente, la naturaleza química de la superficie de la BNC, y por ende su dispersabilidad y compatibilidad relativa con la matriz hidrofóbica de PLA, jugó un rol fundamental en controlar la posibilidad de cristalización del poliéster. Lo anterior es, probablemente, una consecuencia de fenómenos contrapuestos asociados a i) la difusión y plegado de las cadenas de PLA que se ven parcialmente impedidos como consecuencia de la compatibilización (Cyras, D' Amico, & Manfredi, 2017), y ii) los efectos de nucleación inducidos por la dispersión relativa de los refuerzos. (Dai, Cao, & Wang, 2016;Teixeira et al, 2014).…”
Section: Resultados Y Discusiónunclassified
“…of BaTiO 3 . It was observed that the crystallization mechanism of nanocomposite polymers may strongly depend on the intrinsic features of the nanofiller and in consequence its dispersion in the polymeric matrix [33]. For example, in well-dispersed nanocomposites the growing lamellae can influence the disposition of the included nanoparticles, thereby broadening interstitials to allow bulk-like lamellae to form [34].…”
Section: Resultsmentioning
confidence: 99%
“…The crystallization and degree of crystallinity determine the final properties of the resulting polymers. Polymeric crystallization can occur from dilute solutions or the molten state [ 22 ]. In the first case, crystallization occurs by evaporating the solvent, resulting in the appearance of single crystals based on a chain-folded model, which presents aligned chains [ 23 ].…”
Section: Cross-linking Strategies To Obtain Physical Hydrogelsmentioning
confidence: 99%